MODERN METHODS OF ASSESSING THE RISKS OF INSURANCE ORGANIZATIONS (American Journal of Business Management, Economics and Banking, 2025)
This article presents the results of a study on the existing risks in the activities of insurance organizations, the main purpose of risk assessment, assessment invaders, as well as on the foreign methodology for choosing modern methods of assessment, which are used in determining and eliminating risk. Including statistical and expert methods of risk assessment in insurance, risk-free (risk-free) as part of the financial stability loss Risk Assessment Scale, accepted risk, critical risk, catastrophic risk zones, international risk assessment methods risk analysis, stress-test, event tree, Monte Carlo, theoretical opinions and considerations about The Baes trust network are formulated. A comparative analysis of assessment methods was carried out and practical recommendations for their application were formulated. At the same time, in international practice, detailed information about the new stress-testing method of risk assessment, one-variable and multifactorial factors of the method and one-factor and multi-factor models, advantages and disadvantages of the method are presented.